Investigation of the Electrocatalytic reduction of simple ketones in alkaline media - Marth, Axel; Piehler, Julia; Brodt, Matthew; Maier, Maximilian; Thiele, Simon (Electrochemistry Communications, 2025)
Electrochemical energy storage in organic compounds has gained increasing interest recently. In particular, ketones and their secondary alcohols can serve as an electrochemical liquid organic hydrogen carrier (EC-LOHC) due to the possibility of selective oxidation of the hydrogen-rich counterpart. This study examines the possibility of hydrogenating ketones (acetone, 2-butanone, 2-pentanone) in alkaline media (KOH) and shows the influence of aliphatic side-chain length on the surface coverage of the polycrystalline platinum catalyst in an H-cell. This is done by performing linear sweep voltammetry (LSV) and cyclovoltammetry (CV). LSVs reveal similar onset potentials for the ketone reduction reaction, and the influence of onsetting hydrogen evolution reaction and its dependency on surface coverage in the voltage range below 0 V vs. RHE. Furthermore, it reports increased faradaic efficiency (FE) in alkaline media in comparison to acidic media.
CRIS-Team Scopus Importer:2025-01-31